2020
DOI: 10.1177/1094670520944606
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Forget About the Frontline Employee During the COVID-19 Pandemic: Preliminary Insights and a Research Agenda on Market Shocks

Abstract: The COVID-19 pandemic has transformed the way services are delivered. In this editorial, we shine a light on how frontline service employees are coping with the changing work environment. Leveraging insights from a critical incident technique data collection, we identify challenges related to employee morale, interfacing with service consumers, and transformational negative events. We then offer suggestions for future research on these topics. Moreover, we discuss how the business model transformations caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 7 publications
2
112
0
10
Order By: Relevance
“…Patterns of customer demand related to various forms of services, as well as firms’ ability to meet these demands, appear to be increasing in their unpredictability due to environmental disruptions, including pandemics (Voorhees, Fombelle, and Bone 2020), climate change (Besiou and Van Wassenhove 2020), volatile labor markets, unraveling trade relations between nations, and significant societal changes (Previte and Robertson 2019). Our Phase 1 analyses indicated that service providers are under increased pressure to reconfigure, and then deploy, the necessary resources and capabilities to respond to these changes in real time.…”
Section: Service Research Prioritiesmentioning
confidence: 99%
“…Patterns of customer demand related to various forms of services, as well as firms’ ability to meet these demands, appear to be increasing in their unpredictability due to environmental disruptions, including pandemics (Voorhees, Fombelle, and Bone 2020), climate change (Besiou and Van Wassenhove 2020), volatile labor markets, unraveling trade relations between nations, and significant societal changes (Previte and Robertson 2019). Our Phase 1 analyses indicated that service providers are under increased pressure to reconfigure, and then deploy, the necessary resources and capabilities to respond to these changes in real time.…”
Section: Service Research Prioritiesmentioning
confidence: 99%
“…In fact, while much focus has been placed on first responders and healthcare personnel during this time, less attention has been paid to frontline employees (FLEs) in other traditional services (e.g. retail, hospitality), who are referred to as 'forgotten' FLEs (Voorhees et al, 2020). In this regard, the best way to protect the workforce in these essential and highcontact services from getting sick and being at risk is to minimize the dissemination of the infection in the environment where they serve Berry & Stuart, 2020), and practicing physical distancing is thus necessary to secure frontline employees' health.…”
Section: Introductionmentioning
confidence: 99%
“…A study of service workers, likewise, requires a deeper appreciation of well-being issues in both challenging and so-called normal times. Indeed, as noted earlier, while the COVID-19 pandemic has increased public attention on issues related to the vulnerability and precariousness of service work, frontline service work has been characterized even in the best of times by job insecurity, low pay and benefits, and emotional exhaustion (Voorhees, Fombelle, and Bone 2020). Closer to home, our own academic jobs and institutions are undergoing significant changes with diminished opportunities for tenure and job security, increased cost pressures on colleges and universities, and a reframing of what constitutes education (e.g., competencies supplanting diplomas).…”
Section: A Deeper Look At Service Workers’ Experiencesmentioning
confidence: 99%